The internal logic and contradictions of migration control: An excursion into theory and practice in relation to east-west migration - Giorgi, Liana; Pohoryles, Ronald; Pohoryles-Drexel, Sabine; Schmid, Gabriele (Innovation (Abingdon, England), 1992)
The migration problem has acquired a new dimension with the breakdown of State-Communism which has induced new and variable waves of migration out of Eastern Europe. The response of the West to these waves, as well as to the ever-increasing likelihood of emigration from countries of the Third World has been one of mounting regulation. The present article critically juxtaposes the underlying, albeit short-term, logic of regulation with that of East-West migration - itself a highly variated and differentiated process - in an attempt to demarcate a more comprehensive approach to the East-West migration subject.